2003
DOI: 10.1038/sj.ejhg.5201055
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of Huntington disease in Portugal: implications for genetic counselling and clinical practice

Abstract: Huntington disease (HD) is a neurodegenerative, autosomal dominant disorder of late-onset, caused by the expansion of a CAG repeat in the coding region of the gene. Ours is the reference laboratory for genetic testing in HD, in Portugal, since 1998; 90.1% of all 158 families known were identified for the first time, including patients with unusual presentation or without family history. A total of 338 genetic tests were performed: 234 for diagnosis, 96 for presymptomatic and four for prenatal testing (four wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
5
19
1
3
Order By: Relevance
“…The presence of these two mutated alleles in a randomly selected sample of 1,000 individuals from our population could correspond to a higher prevalence of HD in the Portuguese population than described elsewhere. In a previous report, we had predicted it to be at least 2-5:10,0000 (Costa et al 2003), i.e. similar to that of other European countries.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of these two mutated alleles in a randomly selected sample of 1,000 individuals from our population could correspond to a higher prevalence of HD in the Portuguese population than described elsewhere. In a previous report, we had predicted it to be at least 2-5:10,0000 (Costa et al 2003), i.e. similar to that of other European countries.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, haplotype analyses in HD families of different ethnic populations has suggested that multiple mutation events underlie this disorder, and that a specific group of normal unstable alleles within a particular haplotype may be more prone to expansion leading to fully penetrant HD alleles, thus constituting a pool for the generation of new HD genes (Goldberg et al 1993;Squitieri et al 1994;Almqvist et al 1995). Previously, from our routine genetic testing in Portugal, we observed that normal unstable alleles (class 2) had a relatively high frequency, accounting for 3.7% of the ''normal'' chromosomes (Costa et al 2003).…”
Section: Introductionmentioning
confidence: 90%
“…As we have previously reported (Costa et al 2003), among our series of cases for HD diagnosis, we found a high number of HD mutation-negative patients who had both a family history and typical HD clinical features. Here, we describe a series of 107 HDL patients of Portuguese origin, who do not present (CAG) n expansions in the HD gene.…”
Section: Introductionsupporting
confidence: 62%
“…HD was diagnosed in 93% of 618 French and Moroccan (13), 82.8% of 169 Portuguese (14), 57% of 66 Brazilian (15) and 50% of 11 South African black (16) patients with a HDlike phenotype. A review of the literature might suggest a gradient of frequency, where HTT expansions are much more prevalent among North-Europeans, than in other populations.…”
Section: Discussionmentioning
confidence: 99%